2012
DOI: 10.1186/2192-0567-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of hybrid off-grid energy systems by linear programming

Abstract: Background: In this study, a general model of a hybrid off-grid energy system is developed, which can be adjusted to reflect real conditions in order to achieve economical and ecological optimisation of off-grid energy systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Chedid and Rehman [29] proposed an optimal design of wind-solar hybrid system using this technique to minimize the cost of electricity while meeting the load requirements in a reliable manner along with considering environmental factors. Huneke et al [30] used linear programming to obtain optimal configuration for a solar-wind-battery-diesel based power generator combination for two real off-grid energy systems in India and Colombia. The optimization results for both studies show the feasible combination of PV-battery and diesel generator.…”
Section: Linear Programming Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Chedid and Rehman [29] proposed an optimal design of wind-solar hybrid system using this technique to minimize the cost of electricity while meeting the load requirements in a reliable manner along with considering environmental factors. Huneke et al [30] used linear programming to obtain optimal configuration for a solar-wind-battery-diesel based power generator combination for two real off-grid energy systems in India and Colombia. The optimization results for both studies show the feasible combination of PV-battery and diesel generator.…”
Section: Linear Programming Techniquementioning
confidence: 99%
“…[29][30][31][32][33][34] system and compared results with HOMER software and concluded that GA has better accuracy than HOMER. Shadmand and Balog [49] presented Multi-Objective Genetic Algorithm (MOGA) to determine the PV-wind hybrid system design, optimized by considering multiple criteria including size, cost, and availability.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…In a double for loop for the given range of i and j, is calculated for each pair of i and j for the observed period n using expression (10) and taking into account expressions (1)- (9). The obtained matrix of LOLP i,j related to tested i and j is searched for values that are smaller than requested LOLP SET .…”
Section: Description Of the Simplified Modelmentioning
confidence: 99%
“…Merei et al in [8] introduced optimization model of the off-grid hybrid power system for supply of telecommunication base station where they investigated combination of three different battery technologies. Huneke et al, in [9] used linear programming for optimization of hybrid off-grid energy systems. There are many other researches related to optimization and sizing of PV systems such as [10][11][12][13][14][15] and [16].…”
Section: Introductionmentioning
confidence: 99%
“…The model based on Chebyshev polynomials in two steps for short-term dynamics [8]. Huneke et al [9] used the linear programming to obtain an optimal configuration for a combination of generator with wind power -solar energy -battery-diesel for two real powers except for network systems in India and Colombia. The results of optimization for both studies show the possible combination of cells-PV-and diesel generator.…”
Section: Literature Reviewmentioning
confidence: 99%